Learning Motivation as a Relational Experience: Rethinking Student Engagement in Madrasah Education - Rofiqotul Muhiminah; Abdullah (Educazione: Journal of Education and Learning, 2025)
Student learning motivation is one of the important aspects of the learning process because it is related to student involvement during learning activities. However, learning in schools still often shows a gap between the delivery of material and the emotional involvement of students in the classroom. This study aims to understand how teacher interaction, learning atmosphere, and participatory learning activities shape student learning motivation in the madrasah environment. The research uses a qualitative approach with a case study type. Data collection was carried out through learning observations, in-depth interviews, and documentation during learning activities. The research informants consist of teachers, students, and madrasah heads who are directly involved in learning activities. Data analysis is carried out interactively through the process of data condensation, data presentation, and conclusion drawn. The results show that students' motivation to learn develops through more open interpersonal relationships between teachers and students, a comfortable learning atmosphere, and learning that gives students a wider space for participation. Group discussion activities, project-based learning, and non-stressful communication make students more courageous to express their opinions and engage in learning. In addition, the teacher's personal approach helps students feel more valued and comfortable during the learning process. This study shows that learning motivation is not only influenced by learning methods, but also by the quality of social interaction that develops during learning in the classroom.